Gaya Bahasa Novel Tanah Surga Merah Karya Arafat Nur dan Komet Karya Tere Liye - Muhtadin Muhtadin; Rika Berlista; Dian Oktavia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe the style of language used by the novel Tanah Langit Merah and the Comet novel. The research method used is descriptive qualitative. The research data collection technique is the documentation technique. Data analysis techniques are used through data reduction, data presentation and conclusions. The results of this study are: (1) Novel Comet contains a comparative language style of 109 citations, contrasting 39 quotations, linking 31 quotations, and repeating 10 quotations. (2) The novel Tanah Langit Merah contains comparative language styles, 97 parable parables, 117 metaphor quotations, 25 personification quotations, and 1 quote antithesis. (3) antagonism, hyperbole 74 citations, oxymoron 6 quotations, sarcasm 24 quotations, satire 15 quotations, paradox 10 quotations. (4) linkages, 8 excerpt metonemicals, 3 excerpts euphemisms, and 15 citation elepsis. (5) iteration, alliteration of 11 citations, anaphora 4 quotations, and efficiency of 2 quotations. In conclusion, the language style in the novel Tanah Langit Merah and the Comet novel, namely comparative language, conflicting, interrelated, and repetitive Keywords: Language Style, Novel